Interview: "How to Reduce Fallacious Representative Innocence, Word by Word" (response to a questionnaire by Michel Sirvent) - Jean Ricardou (Studies in 20th & 21st Century Literature, 1991)
Interview: "How to Reduce Fallacious Representative Innocence, Word by Word" (response to a questionnaire by Michel Sirvent)
Keywords: Interview; & quot; How to Reduce Fallacious Representative Innocence; Word by Word& quot; response; questionnaire; Michel Sirvent